Research on STEM education with flipped classroom model in the microcontroller development course - Wang, Xiaowei; Sitthiworachart, Jirarat; Ratana-Olarn, Thanin (My University, 2023)
The study investigates the implementation of STEM education with a flipped classroom model in the microcontroller development course. The study aims to identify the needs of students and teachers of the microcontroller course within the framework of STEM education with the flipped classroom teaching model, to develop and implement STEM education with the flipped classroom model in the microcontroller course, to assess and compare students' microcontroller application ability and innovative thinking between experimental and control group. The study adopted both quantitative and qualitative approaches and was carried out in three phases; in phase 1, a needs assessment was done from 100 responded students through a questionnaire which was analyzed through means and standard deviation, while teacher needs were explored by interviewing five teachers and content analysis. In phase 2, flipped classroom model was developed with the help of a focus group interview with 6 experts. While in phase 3, the evaluation of the flipped classroom teaching model's effectiveness was studied through experimental design, and results were drawn by applying MANOVA. The data revealed seven key problems, lack of understanding of students' learning situations, ineffective teaching strategies, encumbered teaching content, teacher-centered classrooms, theoretical teaching, inadequate evaluation, and limited access to hardware. The Flipped Classroom Model can be optimized to improve STEM education and better prepare students for future challenges by providing teacher professional development, adopting diverse and student-centered teaching learning strategies, integrating real-world applications, balancing theory and practice, implementing multi-dimensional evaluation, ensuring access to necessary hardware, and introducing international perspectives.
Keywords: Classroom and STEM education; Flipped classroom model; Growth of domestic industry; Innovative thinking; Microcontrollers application